2020
DOI: 10.1002/smll.202000012
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Atherogenic Effect of Stem Cell Nanovesicles Targeting Disturbed Flow Sites

Abstract: Atherosclerosis development leads to irreversible cascades, highlighting the unmet need for improved methods of early diagnosis and prevention. Disturbed flow formation is one of the earliest atherogenic events, resulting in increased endothelial permeability and subsequent monocyte recruitment. Here, a mesenchymal stem cell (MSC)‐derived nanovesicle (NV) that can target disturbed flow sites with the peptide GSPREYTSYMPH (PREY) (PMSC‐NVs) is presented which is selected through phage display screening of a hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…These features, then, represent significant improvements over the use of stem cell expansion or the collection of cells from patients. Several recent studies have demonstrated the therapeutic value of EVs in musculoskeletal tissue engineering in treating various bone injuries and diseases in vivo. ,, Furthermore, EVs are increasingly recognized as a useful nanomaterial for bone tissue engineering. , Nonetheless, hurdles relating to the complexity and low yield of the purification process have hindered the widespread therapeutic use of exosomes in clinics. Recently, a relatively simple strategy for the generation of exosome-mimetic (EM) nanovesicles with scalable production yields was developed that relies on the self-assembly of the cellular membrane and internal components resulting from the physical extrusion processes of cell sources. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These features, then, represent significant improvements over the use of stem cell expansion or the collection of cells from patients. Several recent studies have demonstrated the therapeutic value of EVs in musculoskeletal tissue engineering in treating various bone injuries and diseases in vivo. ,, Furthermore, EVs are increasingly recognized as a useful nanomaterial for bone tissue engineering. , Nonetheless, hurdles relating to the complexity and low yield of the purification process have hindered the widespread therapeutic use of exosomes in clinics. Recently, a relatively simple strategy for the generation of exosome-mimetic (EM) nanovesicles with scalable production yields was developed that relies on the self-assembly of the cellular membrane and internal components resulting from the physical extrusion processes of cell sources. , …”
mentioning
confidence: 99%
“…Recently, a relatively simple strategy for the generation of exosome-mimetic (EM) nanovesicles with scalable production yields was developed that relies on the self-assembly of the cellular membrane and internal components resulting from the physical extrusion processes of cell sources. 3,12 Nanomaterial-based delivery systems, including EVs, have achieved passive targeting thanks to their extremely small size. Simply put, the ability to move freely through biological barriers provides for the efficient delivery of the vesicles.…”
mentioning
confidence: 99%
“…Hydrogels incorporating various types of nanoerythrocytes were fabricated to evaluate the augmentation capability of cell survival under the limited massive transport environment in the hydrogel. A methacrylated chitosan (MeGC) hydrogel, which is a well-established photoinducible hydrogel system with great biocompatibility and a potential carrier for cell delivery in several studies, was used as a 3D model cell-transplantation system for this investigation. ,, The hydrogel contains more than 95% water and is composed of a polymer network with an interconnected structure. , In general, hydrogels have a large number of nano- or micropores, which can support to contain stable nanoparticles in the hydrogel internal network. , Figure S2A shows the compressive stress–strain curves of the hydrogels with various nanoerythrocytes. The nanoerythrocyte-incorporated hydrogels have a compressive modulus of approximately 10 kPa without significant differences between the hydrogels (Figure S2B).…”
Section: Resultsmentioning
confidence: 99%
“…find that MSC-derived exosomes can restore cardiac contractile function and transform macrophages to M2 phenotype through miR-182 [ 109 ]. Furthermore, peptide GSPREYTSYMPH is used to cross-link with MSC-derived nanovesicles, which can target disturbed flow site and significantly contribute to endothelial recovery after injury [ 110 ]. Due to the targeting ability of natural EVs still needing to enhance, CXCR4 is overexpressed in stem cells through plasmid transfection to acquire robust targeting.…”
Section: The Different Derived Evs For Vascular Therapymentioning
confidence: 99%